Enhanced perception and memory: Insights from synesthesia and expertise. (July 2021) - Ovalle-Fresa, Rebecca; Ankner, Sophie; Rothen, Nicolas
Abstract: Memory research has identified many strategies to enhance memory. However, natural foundations of enhanced memory are vastly underexplored. Interestingly, numerous studies show that synesthesia is associated with enhanced memory performance. Although it has been hypothesized for years that wider changes in visual perception are closely linked with enhanced memory functions in synesthesia, the hypothesis has never been directly put to the test. Here, we investigated whether visual perceptual abilities in synesthesia are linked with higher memory performance by comparing synesthetes who experience colors for letters with non-synesthetic color experts and non-synesthetic individuals from the more general population. Our results showed that synesthesia and expertise share a common profile of enhanced visual perceptual ability and memory in contrast to non-synesthetic individuals from the more general population. Overall, our findings suggest that visual perception and visual memory are more closely connected than previously thought.